A six-week physical therapy exercise program delivered via home-based telerehabilitation is comparable to in-person programs for patients with burn injuries: A randomized, controlled, non-inferiority clinical pilot trial. Issue 1 (February 2023) - Plaza, Anita; Paratz, Jennifer; Cottrell, Michelle
Abstract: Background: Exercise programmes are essential for burn rehabilitation, however patients often have barriers accessing these services. Home-based telerehabilitation (HBT) may be an alternative. This study aimed to determine if exercise programs delivered via HBT were as effective as in-person (IP) programs with respect to clinical outcomes and participant and therapist satisfaction. Methods: A single center, randomized, controlled, non-inferiority pilot trial with blinded assessment was undertaken. Forty-five adults with ≤ 25% total body surface area (TBSA) burns were randomized to receive a 6-week exercise program delivered either by HBT or IP. The primary outcome was burn-specific quality of life (Burn Specific Health Scale – Brief). Secondary outcomes included health-related quality of life, burn scar-specific outcomes, exercise self-efficacy, pain severity, muscle strength and range of motion (ROM). Participant and therapist satisfaction, technical disruptions and adverse events were also recorded. Results: We found no significant within- or between-group differences for any outcome measures except ROM. Achievement of full ROM was significantly different between groups at Week 12 (IP=100% vs HBT=70%, p = 0.005). Non-inferiority was inconclusive. Participant satisfaction was high (median ≥ 9.8/10), with no significant between-group differences. Therapist satisfaction was high (median ≥ 8.9/10), major technical disruptions low (8%) and no adverse events reported. Conclusion: HBT is a safe, effective option to deliver exercise programs for patients with burn injuries ≤ 25% TBSA with comparable clinical outcomes to in-person programmes. Ongoing research is required to further analyze ROM and investigate the effectiveness of HBT for patients with larger burns. Highlights: Exercise programs delivered via home-based telerehabilitation (HBT) achieve similar clinical outcomes to in-person programs. Non-inferiority remains inconclusive and ROM outcomes require further investigation. Participant satisfaction was high and not significantly different between groups. HBT is safe, with minimal technical disruptions and high therapist satisfaction. Further trials are required for patients with> 25% TBSA burn injuries.